Influence of Member Income on Table Banking Adoption Among Rural Households A survey of Machakos County, Kenya - Kioko, Daniel Mutungi; Ng’ang’a, Prof. Irura; Maina, Dr. Lucy Kiganane (Advances in Social Sciences Research Journal, 2015)
The purpose of the study was to assess influence of the income level on table banking adoption. The study was guided by social capital theory and employed descriptive survey and explanatory research design. The target population was 1084 members of table banking groups in Machakos County. Simple random sampling technique was used to select a sample size of 188 members. The researcher used questionnaires to collect data from members of the group and interview schedule to collect data from table banking group leaders. Data on demographics was analysed by descriptive statistics which included means, frequencies and percentages. Hypothesis was tested by multiple regressions with the aid of SPSS. Results were presented in form of tables, graphs and charts. The study revealed that there is a negative and significant relationship between members’ income (r=-0.163, p=0.032) <0.05) and table banking adoption. This means that the higher the income, the less likely they are to adopt table banking. Thus, encouraging the members to participate in formal and beneficial social networking would go a long way in making sure that the members are well informed in terms of improvement of their saving culture through the adoption of table banking.